Diversity of the population of Tick-borne encephalitis virus infecting Ixodes ricinus ticks in an endemic area of central Switzerland (Canton Bern) - Casati, Simona; Gern, Lise; Piffaretti, Jean-Claude (My University, 2006)
Tick-borne encephalitis virus (TBEV), a member of the genus Flavivirus, has a positive-strand RNA genome containing a single open reading frame flanked by non-coding regions (NCRs). Ixodes ricinus ticks (n = 307) were collected from vegetation in a natural TBEV focus in Belp, Switzerland. The presence and identity of the virus were determined by nested RT-PCR followed by sequencing of the 5'-terminal region that comprises the 5' NCR and the capsid-encoding region (C). The presence of the western European TBEV subtype (W-TBEV) genome was detected in 14.3% of the ticks. Nucleotide sequence analysis revealed a high variability of 55.5%. In particular, four DNA fragments (CS 'A', CS 'B', the folding-stem structure and the start codon) showed substantial heterogeneity, which has the potential of compromising replication, translation and packaging of the viral genome. This variability may reflect a viral strategy to select the fittest RNA molecule to produce a viral infection in the different vertebrate hosts that may be encountered by the ticks. It may also indicate a possible ancient introduction of TBEV to the Belp site. In addition, it may contribute to explaining the annual low incidence of tick-borne encephalitis in the natural focus of Belp, despite the high prevalence of TBEV genomes in ticks.
Keywords: NATURAL FOCI; FLAVIVIRUS; DISEASES; SEQUENCES; REGION; EUROPE; PCR